Lehninger principles of biochemistry / David L Nelson; Michael M Cox - Nelson, David L.
'The UNDERSTAND! Biochemistry CD is a self-paced study tool that allows students to review, visualize, and test their mastery of biochemistry! There are 65 "Minicourses" organized as self-contained tutorials on key subject areas in biochemistry! (inside front cover).